Psychosis Assessment in Early-Stage Parkinson’s Disease: Comparing Parkinson’s Psychosis Questionnaire with the Brief Psychiatric Rating Scale in a Portuguese Sample - I. Cargaleiro; M. Serra; J. Alves da Silva; B. Neto; M. Gonçalves-Pereira; P. Bugalho (Parkinson's Disease)
Psychotic symptoms in Parkinson’s disease (PD) are frequent, disabling, and an important prognostic factor. Thus, screening instruments for detecting psychosis in PD are needed. For this purpose, we applied the Parkinson’s Psychosis Questionnaire (PPQ), a short structured questionnaire, which requires no specific training, along with the Brief Psychiatric Rating Scale, expanded version (BPRS-E), for rating general psychopathology, including psychotic symptoms. We evaluated, in a cross-sectional study, a Portuguese sample of 36 early-stage PD patients (mean age of 73 years; mean duration of illness of 3.2 years). The PPQ total score correlated with the BPRS-E total score (0.359; 𝑃=0.032) and with the BPRS-E-positive symptoms score (0.469; 𝑃=0.004). The prevalence of psychosis (41.7%) was higher than expected. Sampling bias and detection of minor psychotic phenomena may have contributed to this result. These findings suggest that the PPQ should be further evaluated as a feasible assessment for psychotic symptoms in PD.